Info SUSURGALUR edutainment, Maret 2015 - SUSURGALUR, Editor Journal (SUSURGALUR, 2015)
This journal, with ISSN 2302-5808, was firstly published on March 24, 2013. Since issue of September 2013, the SUSURGALUR journal has jointly been organized by the Lecturers of APB UBD (Academy of Brunei Studies, University of Brunei Darussalam) and the Lecturers of International and Historical Study Program FASS (Faculty of Arts and Social Sciences) UBD in Bandar Seri Begawan, Brunei Darussalam; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every March and September.Â